2017
DOI: 10.4194/1303-2712-v17_3_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aquafeed industry is facing the lack of availability of fish meal and oil. The need of an economic and environmental sustainability has increased the use of plant-derived oils. In order to provide an overview of which ingredients are the most frequently used in GSB diet and as they affect the lipid composition of aquafeeds , we analyzed 26 feed samples collected from farmers. At the same time, 44 farmed GSB were analyzed to compare the fatty acid (FA) composition with 21 wild GSB and 46 GSB farmed in 2005.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…2.5%), consistent with diet composition. Vasconi et al [38] compared the fatty acid composition of the muscle from farmed seabream, collected in 2005 and 2014, reporting similar values to those of our study for C16:0, C18:1 n-9, ALA, and EPA contents. However, they attained lower amounts of C18:2 n-6 (12.47 to 16.7%) and higher contents of DHA (11.95 to 15.57%).…”
Section: Nutritional Composition and Fatty Acid Profile Of S Aurata M...supporting
confidence: 86%
“…2.5%), consistent with diet composition. Vasconi et al [38] compared the fatty acid composition of the muscle from farmed seabream, collected in 2005 and 2014, reporting similar values to those of our study for C16:0, C18:1 n-9, ALA, and EPA contents. However, they attained lower amounts of C18:2 n-6 (12.47 to 16.7%) and higher contents of DHA (11.95 to 15.57%).…”
Section: Nutritional Composition and Fatty Acid Profile Of S Aurata M...supporting
confidence: 86%
“…Other authors [ 74 ] observed that the fatty acid profile of seabream reflected the fatty acid contents of the feeds used in their feeding. The muscles of wild gilthead seabream contained more n-3 PUFAs (38.79%) and a higher n-3/n-6 ratio (3.91) than the farmed seabream (22.71 and 26.12%, 1.24 and 2.04, respectively) [ 75 ]. The authors observed a reverse regularity for n-6 PUFAs (10.95% for wild fish and 13.91 or 19.23% for farmed fish).…”
Section: Discussionmentioning
confidence: 99%
“…The aquafeed industry is facing a lack of availability of fish meal and oil. The need for economic and environmental sustainability has increased the use of plant-derived oils and for that, it is making efforts to reduce the dietary inclusion of marine ingredients, searching alternative dietary proteins and lipid sources, and formulating more efficient eco-friendly feeds [38]. In addition to the above, product quality and its service characteristics would naturally pave the way for a consumer, bringing about his satisfaction and ultimately, gaining his loyalty [39].…”
Section: Comparative Study Between Methodology (Cata Vs Pm)mentioning
confidence: 99%